Adaptação de jogos digitais para jogos de tabuleiro - Martins, José Arthur Vigilante (2021)
Board games are, with no doubt, an old entertainment media and have always had their social importance. This study aims to reach the possible application of a methodology to assist in the post-modern movement of adapting digital to board games. Passing trough what an adaptation is, its forms of engagement and why an adaptation is made. With a methodology to identify the main points of the original work, the core, the essence of the digital game to be transferred to the board game, which goes far beyond the traditional narrative as the main tool of transference from one media to another. In games we have a much greater impact of the mechanics, their challenges and gameplay, this is the essence that cannot be forgotten and should provide an experience that the player can create within his mind a connection with the main work in order to not interfere in your desired experience. In order to qualify the methodology, the analysis of games already adapted in the market will be made considering the review and the experience of the community and critics by applying the triad: Game Mechanics, Challenges and Narrative to identify the possible mistakes and success